2014
DOI: 10.1002/sim.6095
|View full text |Cite
|
Sign up to set email alerts
|

A toolkit for measurement error correction, with a focus on nutritional epidemiology

Abstract: Exposure measurement error is a problem in many epidemiological studies, including those using biomarkers and measures of dietary intake. Measurement error typically results in biased estimates of exposure-disease associations, the severity and nature of the bias depending on the form of the error. To correct for the effects of measurement error, information additional to the main study data is required. Ideally, this is a validation sample in which the true exposure is observed. However, in many situations, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
108
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 56 publications
0
108
0
Order By: Relevance
“…Cases had a lower intake of fish and higher intake of meat fat. 3 One participant each was missing information on supplemental vitamin E use and supplemental calcium use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cases had a lower intake of fish and higher intake of meat fat. 3 One participant each was missing information on supplemental vitamin E use and supplemental calcium use.…”
Section: Discussionmentioning
confidence: 99%
“…These correlation magnitudes, which broadly reflect strength of serum and urine multiple-metabolite prediction of diet based on statistical modeling (i.e., prediction based on a training data set and testing with the use of a testing data set), were generally comparable in serum and urine, with evidence that results did not Values may not sum to 100% because of rounding. 3 Comparison by case-control status was significant at P , 0.05 on the basis of a chi-square test for categorical variables and a t test for continuous variables. 4 Calculated by adding the number of times per week engaged in moderate-intensity leisure-time physical activity plus 2 times the number of times per week engaged in vigorous-intensity leisure-time physical activity.…”
Section: Urine and Serum Comparisonmentioning
confidence: 98%
See 1 more Smart Citation
“…Most studies rely on self-reported intakes from food frequency questionnaires (FFQ), which are known to suffer from relatively large systematic and random measurement errors [4]. Accurate whole grain intake data acquisition via FFQ may be hampered by having few questions on cereal foods, difficulties among consumers in recognizing whole grain products, large variations in whole grain content in cereal foods and lack of food composition data [5]. Therefore, dietary biomarkers may provide an independent tool to overcome some of these obstacles and a better way for objective ranking of whole grain intake in epidemiological studies [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…regression calibration 19, 20 ) have been used to adjust risk-outcome associations for measurement bias, but also require a biomarker with high sensitivity and specificity. STIs, for example, are imperfectly sensitive as markers for condomless sex since one may engage in the behavior but not become infected with an STI.…”
Section: Introductionmentioning
confidence: 99%